Selecting a Church Planting Model That Works - Steffen, Tom A. (Missiology, 1994)
Unlike a decade ago, a plethora of church planting models now exists from which church planters can select. New models continue to roll off the presses. While the multiplication of models provide valuable new insights into the ambiguous task of church planting, they also create a new dilemma. How can church planters select or design a church planting model that matches a specific people group? This article critiques six church planting models, probes how the church planter's personal philosophy and vision impacts such selection, and provides a two-dimensional model to show how to wade through the options and craft an effective church planting model for a specific people group.